“SEHATKU” BOOK MODIFICATION FOR DISEASE PREVENTION IN THE SURABAYA DIASPORA COMMUNITY - Ritunga, Imelda; Setijowati, Nanik; Mellyanawati, Mellyanawati; Santoso, Jemima Lewi; Wartiningsih, Minarni; Jasin, Jessica Lingga; Soplantila, Chelsy Gravia; Maelo, Clara Angraini; Himawan, Asavita Rhena; Wilmida, Anggun Diah; Zhakia, Jelita Zhufatul; Pardosi, Delima Silvani; Mahulette, Aisyah Nurulhisa; Paskadita, Nafiri Eldya (LPPM Univ. Ibn Khaldun Bogor, 2025)
The epidemiological shift from communicable to non-communicable diseases poses a significant challenge in today’s health development efforts. Preventing chronic diseases has become a shared priority, one of which is through routine health screenings. The large number of adult and elderly members in the GBI Diaspora community highlights the need for health examinations as a concrete step in disease prevention. Psychological and financial barriers, along with often-overlooked documentation issues, can hinder individuals from undergoing health checks. A health record system was proposed as a solution through a mini project at GBI Diaspora Sejahtera Surabaya, delivered alongside health screening activities. The implementation involved collaboration and coordination in designing the “SEHATKU” pocketbook, which was distributed during the screenings. A total of 71 GBI Diaspora participants underwent health screenings and received the “SEHATKU” pocketbook as a tool for recording results and providing education. Post-activity questionnaires completed by 65 participants showed that more than 50% demonstrated increased knowledge and awareness of the importance of regular health check-ups. With the use of the “SEHATKU” pocketbook, proper documentation supports ongoing individual health monitoring within the community. Regular health screenings accompanied by the distribution of the “SEHATKU” pocketbook represent a promotive and preventive measure for non-communicable disease prevention at the primary care level.